ISLAMIC EDUCATION IN SRI RATU TAJUL SAFIATUDDIN’S PERIOD (HISTORICAL REVIEW) - Putra, Rahmad Syah (Ar Raniry : International Journal of Islamic Studies, 2015)
The background of this study is to see how the Islamic education in Sri Ratu Tajul Alam Safiatuddin’s period, at that time the kingdom of Aceh Darussalam peak of its glory (Century XVII), it was visited by many scholars (Ulama and the Poet), foreign and domestic. Among those who came, there are some scholars who stayed in Aceh and return to his homeland as well. While in Aceh, they became a teacher, especially in the science of religion and the author of books on various branches of science. Since the number of teachers and authors who live in Aceh make Aceh as "Qibla" the study of Islam and other sciences in the archipelago at that time. The purpose of this study was to determine how the system of Islamic education in the XVII century (1050-1086 H = 1641-1675 AD), the progress and the development of Islamic education in Aceh during the reign of Sri Ratu Tajul Alam Safiatuddin and compliance with the current context. Data from this study were obtained through the collection of a variety of references and relevant sources, then in their analysis authors use literature review, the results of the processing of these data are concluded that the Islamic Education In Sri Ratu Tajul Alam Safiatuddin’s period was very advanced, because he encouraged the importance of education and science when he lead, at that time science and education in Aceh were developed so well, the literature of Malay-Aceh was very well-known to all over the world.